Nucleic Acid Sensing in Invertebrate Antiviral Immunity - Wang, Pei-Hui; He, Jian-Guo (International review of cell and molecular biology, 2019)
Innate immunity is an ancient and conserved defense mechanism against infectious agents. It is activated after pathogen-associated molecular pattern sensing by germline-encoded pattern-recognition receptors, including specialized nucleic acid sensors. In vertebrates, nucleic acid sensing activates the dominant antiviral pathway that induces interferon (IFN) response and enhances antigen-specific adaptive immunity. Although canonical IFN system is absent in invertebrates, nucleic acid stimulation, and viral infection trigger an inducible non-specific antiviral response that exhibits multiple similarities to vertebrate IFN system. Invertebrates lack the adaptive immunity that provides long-term antigen-specific protection from pathogens. Meanwhile, the RNA interference (RNAi) pathway senses viral nucleic acids and triggers the sequence-specific degradation of viral RNAs, thereby representing a specific antiviral mechanism of invertebrates. RNAi provides the primary antiviral response in some invertebrates but plays minimal or no role in vertebrate antiviral immunity. This review summarizes the nucleic acid sensing-mediated antiviral immunity in invertebrates.